1, 4-Dithiothreitol mediated cleavage of the acetal and ketal type of diol protecting groups. Issue 16 (4th April 2018) - Liu, Yan; Zeng, Jing; Sun, Jiuchang; Cai, Lei; Zhao, Yueqi; Fang, Jing; Hu, Bo; Shu, Penghua; Meng, Lingkui; Wan, Qian
Abstract : An efficient deprotection of the ketal and acetal type protecting groups has been achieved with Brønsted acid as a catalyst and 1, 4-dithiothreitol as a ketal or acetal exchange reagent. Abstract : The use of 1, 4-dithiothreitol (DTT) as an acetal or ketal exchange reagent and camphorsulfonic acid (CSA) as a catalyst permitted the efficient removal of benzylidene acetal and isopropylidene ketal protecting groups under mild conditions. A variety of acetal and ketal protected carbohydrates were deprotected with this method in 78–98% yields. In addition, terminal isopropylidene ketal or benzylidene acetal was selectively cleaved in the presence of internal isopropylidene ketal. Moreover, it was found that an unusual seven-membered 1, 3-dithiepane was formed during the deprotection of benzylidene acetal with DTT.